Higher biosecurity level was associated with reduced risk of Danish dairy cattle farms becoming test-positive for Salmonella Dublin in a nested case–control study - Lars Pedersen; Lars Pedersen; Hans Houe; Erik Rattenborg; Liza Rosenbaum Nielsen (Frontiers in Veterinary Science)
Salmonella Dublin (S. Dublin) is a cattle-adapted bacterium with enzootic occurrence in cattle populations of many countries. Preventing the spread of S. Dublin between cattle farms requires an understanding of the local pathways for the direct and indirect transmission of bacteria. Identifying key risk factors is complicated due to the numerous pathways through which the bacteria can be introduced and established on dairy cattle farms. This study aimed to provide new knowledge about the effect of biosecurity in dairy farms in S. Dublin-enzootic areas of Denmark. The association between the researcher-assessed biosecurity level and the risk of introducing and establishing S. Dublin in farms was investigated by following a monthly recalculated cohort of dairy farms with no test-positive S. Dublin surveillance results over the previous 2 years. There were 37 new test-positive farms matched by herd size with 74 control farms that remained test negative in the mandatory S. Dublin surveillance programme. A published Biosecurity Assessment Framework for S. Dublin (BAF-SD) was used to systematically and semi-quantitatively assess the on-farm biosecurity practices across 12 farm sections. Each section was scored on a scale from 0 (total lack of biosecurity measures) to 100 (excellent biosecurity) based on observations and interviews. Lower biosecurity scores in the sections” entrance area,” “pick-up-delivery of calves,” “calves < 130 days,” “cattle > 130 days,” and “storage of feed and feeding” were associated with becoming test-positive for S. Dublin at a 90% confidence interval (CI) level in univariable logistic analyses. In the multivariable analysis, a higher weighted biosecurity score across all sections was found to be associated with (p < 0.05) with lower odds of becoming test-positive for S. Dublin (odds ratio [OR] = 0.64 per 10-unit increase in biosecurity level). None of the study farms had very good (score 80 to <90) or excellent biosecurity (score of 90 or above), highlighting the opportunities for biosecurity improvements on-farm. In conclusion, the current biosecurity levels in Danish farms appear insufficient to resist the infection pressure of S. Dublin from the farm surroundings. Hence, biosecurity practices need to be improved, and/or the infection pressure needs to be reduced, to lower the number of new test-positive dairy cattle farms in Denmark.